Health Impact Assessment of Public Policies on Community Vegetable Consumption Promotion - Kunset, Pikuntip; Rueanchan, Sitthiphan (Nursing Research and Innovation Journal, 2023)
This action research aimed to evaluate the health impact of public policies on community vegetable consumption promotion at Khao Phra Bat Subdistrict, Nakhon Si-Thammarat Province. The conceptual framework was based on the Health Impact Assessment (HIA). The primary target group included 398 family delegates. The secondary target group comprised 50 leaders, including a sub-district administrative organization, health personnel of a sub-district health promotion hospital, community leaders, village committees, and village health volunteers. Data collection included surveys, in-depth interviews, and focus group discussions. The research comprised two phases: 1) preparation and 2) implementation of health impact assessment. Research instruments included the household consumption and vegetable cultivation survey, in-depth interview, and semi-structured interview. The quantitative data were analyzed using descriptive statistics, and the qualitative data were analyzed by content analysis. The results revealed that: 1) in the preparation phase, a working team of 45 persons was established to study the community vegetable consumption and planting; and 2) in the implementation of the health impact assessment phase, the results revealed that herb vegetables are commonly cultivated by families for cooking. Regarding the sub-district policy, it was found that the budget support for planting and consuming vegetables covered only some villages. Based on these results, the policy recommendation included developing vegetable-based menus for school-age children, enhancing understanding regarding food safety and vegetables among community stores, promoting vegetable cultivation that requires minimal water usage and can be implemented in containers, and supporting budget allocation for vegetable cultivation and consumption to cover all villages. Therefore, public health personnel should evaluate the health impact of public policies to develop guidelines for promoting community vegetable consumption and emphasize the importance of involvement from various sectors in assessing and establishing community public policies to ensure the sustainability of community health. Keywords: Health impact assessment, Public policy, Vegetable consumption promotion